The (conceptions of) European identity of pupils in the border region of Rhineland-Palatinate - Saskia Langer (Culture, Practice & Europeanization, 2023)
Do you identify with Europe, and if so, why? 248 lower secondary school students answered this question in a survey conducted in Rhineland-Palatinate, Germany. The area is part of the so-called Greater Region, which is a cross-border region between Germany, France, Luxemburg and Belgium with the possibility of a transnational everyday-life. The aim of the article is to give space to the pupils’ perspectives on their felt identity as well as to reflect on the importance of the border region for their justification of identifying with Europe. The justifications of the students offer a new perspective: the patterns of reasoning not only indicate different reasons for identity, but also a variety of conceptions of Europe, and refer to different levels and dimensions of social identity. While no correlation between proximity to the border and their identification with Europe could be found, individual practices, such as crossing the border freely, were students’ preferred justification for European identity. Because the students were capable of independently arguing their position on European identity, this article suggests to treat European identity as a topic in school giving students the opportunity to reflect on the contested nature of Europe and European identity in class.